2012
DOI: 10.1186/1556-276x-7-652
|View full text |Cite
|
Sign up to set email alerts
|

CuInS2 quantum dot-sensitized TiO2 nanorod array photoelectrodes: synthesis and performance optimization

Abstract: CuInS2 quantum dots (QDs) were deposited onto TiO2 nanorod arrays for different cycles by using successive ionic layer adsorption and reaction (SILAR) method. The effect of SILAR cycles on the light absorption and photoelectrochemical properties of the sensitized photoelectrodes was studied. With optimization of CuInS2 SILAR cycles and introduction of In2S3 buffer layer, quantum dot-sensitized solar cells assembled with 3-μm thick TiO2 nanorod film exhibited a short-circuit current density (Isc) of 4.51 mA cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…The photoelectrochemical responses obtained in our study are higher than the values reported previously for various sensitized-TiO 2 photoelectrodes. 4,5,7,15,51,60,56,63 Also, the results obtained in this study are in agreement with results reported by Yang et al 44 The electronic properties of sensitized and unsensitized TiO 2 NTA lms were determined using the Mott-Schottky (MS) method. The measurements were performed at a frequency of 100 Hz, with the potential scan range from 0.5 to À1 V (vs. SCE) under illumination.…”
Section: Photoelectrochemical Measurementssupporting
confidence: 91%
“…The photoelectrochemical responses obtained in our study are higher than the values reported previously for various sensitized-TiO 2 photoelectrodes. 4,5,7,15,51,60,56,63 Also, the results obtained in this study are in agreement with results reported by Yang et al 44 The electronic properties of sensitized and unsensitized TiO 2 NTA lms were determined using the Mott-Schottky (MS) method. The measurements were performed at a frequency of 100 Hz, with the potential scan range from 0.5 to À1 V (vs. SCE) under illumination.…”
Section: Photoelectrochemical Measurementssupporting
confidence: 91%
“…Zhou et al reported QDSSCs based on CuInS2 and introduction of In2S3 buffer layer suing SILAR process, which presented as high as ~1.06% PCEs [16]. However, the lower photovoltaic performance of QDSSC is due to severe charge recombination process at the interface of the TiO2/QD/electrolyte interface.…”
Section: Of 11mentioning
confidence: 99%
“…Zhou et al prepared QDSSCs based on CuInS 2 and introduction of In 2 S 3 buffer layer suing SILAR process, which presented as high as~1.06% PCEs [16]. Meng et al developed a CuInS 2 QDs on reduced graphene oxide sheets using facile one-pot solvothermal approach and delivered a PCE of 1.5% [17].…”
Section: Introductionmentioning
confidence: 99%